The Scope of Differentiated Instructional Materials in Pancasila Education Learning at State Senior High School 9 Ambon - Marita Soamole; Lisye Salamor; Fatimah Sialana; Rita Fransina Maruanaya (Mindset : Jurnal Pemikiran Pendidikan dan Pembelajaran, 2025)
The implementation of differentiated instruction has become a key strategy within the Merdeka Curriculum to address students’ diverse learning needs, particularly in Pancasila Education. This approach enables teachers to design more inclusive, meaningful, and learner-centered instructional strategies that align with students’ individual potentials. This study aims to analyze the scope of differentiated instructional materials covering content, process, input, and product in Pancasila Education learning at State Senior High School 9 Ambon. A descriptive survey method was employed, using closed-ended questionnaires distributed to Grade X students at State Senior High School 9 Ambon. The results indicate that the level of implementation of differentiated content reached 89.13%, differentiated process 86%, differentiated input 84.78%, and differentiated product 84.78%. These percentages reflect teachers’ consistent efforts to adapt instructional practices to students’ needs and characteristics across multiple dimensions of learning. The findings demonstrate that differentiated instructional materials are effective in enhancing students’ active participation and conceptual understanding in Pancasila Education, as they accommodate differences in learners’ interests, readiness levels, and learning styles. Therefore, continuous and systematic professional development for teachers is essential to ensure that differentiated instructional strategies are implemented optimally, consistently, and in alignment with students’ learning needs.